Microcolony Imaging of Aspergillus fumigatus Treated with Echinocandins Reveals Both Fungistatic and Fungicidal Activities - Ingham, Colin J.; Schneeberger, Peter M. (PLOS ONE, 2012)
Background The echinocandins are lipopeptides that can be employed as antifungal drugs that inhibit the synthesis of 1,3-β-glucans within the fungal cell wall. Anidulafungin and caspofungin are echinocandins used in the treatment of Candida infections and have activity against other fungi including Aspergillus fumigatus. The echinocandins are generally considered fungistatic against Aspergillus species. Methods Culture of A. fumigatus from conidia to microcolonies on a support of porous aluminium oxide (PAO), combined with fluorescence microscopy and scanning electron microscopy, was used to investigate the effects of anidulafungin and caspofungin. The PAO was an effective matrix for conidial germination and microcolony growth. Additionally, PAO supports could be moved between agar plates containing different concentrations of echinocandins to change dosage and to investigate the recovery of fungal microcolonies from these drugs. Culture on PAO combined with microscopy and image analysis permits quantitative studies on microcolony growth with the flexibility of adding or removing antifungal agents, dyes, fixatives or osmotic stresses during growth with minimal disturbance of fungal microcolonies. Significance Anidulafungin and caspofungin reduced but did not halt growth at the microcony level; additionally both drugs killed individual cells, particularly at concentrations around the MIC. Intact but not lysed cells showed rapid recovery when the drugs were removed. The classification of these drugs as either fungistatic or fungicidal is simplistic. Microcolony analysis on PAO appears to be a valuable tool to investigate the action of antifungal agents.